Endothelial dysfunction in renal interstitial fibrosis - Perry, Heather M. (Nephron, 2016)
Kidney disease affects millions of people worldwide and it is now widely accepted that many pathological processes may persist after AKI that can cause the progression to CKD. Tubulointerstitial fibrosis manifests soon after injury and while many cellular and molecular components of kidney fibrosis have been discovered, largely in animal models, new therapeutic strategies are still desperately needed. The renal endothelium has emerged as important in progression of fibrosis through regulation of hypoxia, inflammation, and cellular crosstalk. This review aims to highlight our current understanding of the role of the endothelium in interstitial fibrosis and to identify potential therapeutic targets.